The effect of prenatal maternity leave on short and long-term child outcomes - Alexander Ahammer; Martin Halla; Nicole Schneeweis (Johannes Kepler University Linz, Christian Doppler Laboratory Aging, Health and the Labor Market, 2018)
Maternity leave policies are designed to safeguard the health of pregnant workers and their unborn children. However, little is known about the impact of existing policies, which are not evidence-based. We evaluate a maternity leave extension in Austria, which increased mandatory leave from 6 to 8 weeks prior to birth. We exploit that the eligibility for the extended leave was determined by a cutoff due date. Our estimates capture a reduction of in utero exposure to maternal stress caused by work in the third trimester of pregnancy. We find no evidence for significant effects of this extension on children's health at birth or long-term health and labor market outcomes. Subsequent maternal health and fertility are also unaffected. We conclude that, for workers without problems in pregnancy, mandatory maternity leave should not start prior to the 35th week of gestation.
Keywords: J13; I18; J28; I13; J83; J88; 330; maternity leave; fetal origins hypothesis; infant health; birth outcomes; birth weight; long-term child outcomes; fertility